ASSESSING GLOBAL CLIMATE VARIABILITY UNDER COLDEST AND WARMEST PERIODS AT DIFFERENT LATITUDINAL REGIONS - Runtunuwu, Eleonora; Kondoh, Akihiko (Indonesian Journal of Agricultural Science, 2008)
Effect of climate change on water balance will play a key rolein the biosphere system. To study the global climate changeimpact on water balance during 95-year period (1901-1995),long-term grid climatic data including global mean monthlytemperature and precipitation at 0.5 x 0.5 degree resolutionwere analysed. The trend and variation of climate change, thetime series of monthly air temperature and precipitation datawere aggregated into annual arithmetic means for two extremeperiods (1901-1920 and 1990-1995). The potential evapotranspiration(Eo) was calculated using Thornthwaite method.The changes in mean annual value were obtained by subtractingthe maximum period data from 1990 to 1995 (Max) with theminimum period data from 1901 to 1920 (Min). The resultsrevealed that over 95-year period, mean global air temperatureincreased by 0.57oC. The temperature increase varied greatlyin Asia, with more than 3.0oC, especially at 45-70oN, as wellover the northern part of America (60-65oN) and Europe (55-75oN). In low latitude across Asia, Africa, and South America,the variation was less than 1.5oC. In 80-85ºN region, thevariation was relatively small and at higher latitudes it increasedsignificantly. Precipitation varied temporally and spatially. Inthe 40-45ºN and 40-45ºS regions, increasing precipitation ofmore than 100 mm occurred during the June-August andSeptember-November, especially in the northern hemisphere.The Eo increase of 2000 mm during 95 years occurred in thetropical northern America, middle Africa, and South-East Asia.A grid in Central Java of Indonesia showed that the Eo increaseof 2500 mm during 95 years resulted in the decrease of growingperiod by 100 days. In coping with climate change, adjustmentof cropping calendar is imperative.